Cultural- and traditional-ecological perspectives in Saami religion - Fjellström, Phebe (Scripta Instituti Donneriani Aboensis, 1987)
The period of Christmas peace, established by the Hälsinge law, was a firmly established custom in the Nordic countries going back to the official Christmas celebrations laid down by the Catholic church at Tours in 867. Christmas Eve was respected as a day of fasting and "no meat was eaten", beliefs about Christmas folk were common in western Scandinavia and Celtic areas, –the Catholic celebrations of the twelve days of Christmas—the period of Christmas peace—was linked with these beliefs and the sacrificial rite took place relatively close to the tent with a sacrificial dish shaped like a boat complete with sail and oars being hung up in a tree, probably a tall tree so that the Christmas folk could reach it on their wanderings through the air. This last that-clause does not seem to have any Catholic connections but rather pre-Christian ones. An analysis of these different phenomena can perhaps provide us with examples of parallel phenomena in Saami materials.